Isolation and Characterization of Phosphate-solubilizing Bacteria from Rice Field of Odisha and Their Growth Promoting Effect on Agricultural-Sectors. Issue 2 (1st February 2023) - Samal, D P Krishna; Sukla, Lala Behari
Abstract: Organic farming will be a significant approach for farmers in the coming decades due to improved production and the preservation of soil natural properties. Phosphorus is the second most macronutrient required for plants to survive. The primary goal of this research was to know the paddy field soil nutritional status and isolate potential PSB bacteria from soil samples, which may aid in the development of a potent biofertilizer for organic farming. 12 soil samples were collected from three districts of Odisha (Kendrapara, Cuttack, Khordha). A laboratory study was conducted to isolate, identify, and characterise phosphate solubilizing bacteria from rice field soil. The morphological and biochemical traits of the PSB strains were evaluated. Four potential PSB strains PR, PA, PD, PS were chosen based on solubilization zone production and abundance in sampling site. The isolates PR had maximum phosphate solubilization index of 2.72 in pikovskaya agar medium and were strongly predominant in all regions. Phosphate solubilization and enhanced germination potential were evident in all four species. When compared to controls, good plant height, dry weight, and fresh weight were confirmed in seed germination assays with all bacterial isolates. The PR strain had the highest rate of germination 96.03%.